MHC class II proteins and disease: a structural perspective - Jones, E; Fugger, L; Strominger, J; Siebold, C (Macmillan Publishers Ltd., 2006)
MHC class II molecules on the surface of antigen-presenting cells display a range of peptides for recognition by the T-cell receptors of CD4⁺ T helper cells. Therefore, MHC class II molecules are central to effective adaptive immune responses, but conversely, genetic and epidemiological data have implicated these molecules in the pathogenesis of autoimmune diseases. Indeed, the strength of the associations between particular MHC class II alleles and disease render them the main genetic risk factors for autoimmune disorders such as type 1 diabetes. Here we discuss the insights that the crystal structures of MHC class II molecules provide into the molecular mechanisms by which sequence polymorphisms might contribute to disease susceptibility.